2014
DOI: 10.9790/487x-16526172
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Quality Management Systems on the Performance of Food Processing Firms in Kenya

Abstract: Abstract:The impact of quality management systems (QMS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 63 publications
0
8
0
7
Order By: Relevance
“…TQM se puede implementar en cualquier tipo de organización y que existe una relación positiva con el desempeño de la empresa (Jaafreh, 2013), lo que significa que TQM permite a las organizaciones alcanzar mayores resultados financieros, operacionales (Kibe & Wanjau, 2014) y mejorar su posición en el mercado, son estos los motivos que posee una alta aceptación en el campo empresarial (Giménez, Jiménez, & Martinez, 2014), (Santos & González, 2008).…”
Section: Gestión Total De La Calidad (Tqm -Total Quality Management)unclassified
See 3 more Smart Citations
“…TQM se puede implementar en cualquier tipo de organización y que existe una relación positiva con el desempeño de la empresa (Jaafreh, 2013), lo que significa que TQM permite a las organizaciones alcanzar mayores resultados financieros, operacionales (Kibe & Wanjau, 2014) y mejorar su posición en el mercado, son estos los motivos que posee una alta aceptación en el campo empresarial (Giménez, Jiménez, & Martinez, 2014), (Santos & González, 2008).…”
Section: Gestión Total De La Calidad (Tqm -Total Quality Management)unclassified
“…Amplia literatura ha identificado los principales beneficios de la gestión total de la calidad: mejora de la calidad de productos y servicios, aumenta la satisfacción de los clientes y empleados, reducción de costos, mejora el desempeño financiero, aumenta la competitividad, incrementa la productividad, aumento de la autonomía de los empleados, incrementa la motivación de los empleados, repercusión en la innovación y la mejora continua (Kibe & Wanjau, 2014) (Zehir, Ertosun, Zehir, & Müceldilli, 2012) (Jaafreh, 2013) (Chen, Anchecta, Lee, & Dahlgaard, 2016) (Martínez, 2011) (Santos & González, 2008).…”
Section: Gestión Total De La Calidad (Tqm -Total Quality Management)unclassified
See 2 more Smart Citations
“…In the previous study, (Cornelison, 2013) identified a number of benefits by implementing TQM. (Prajogo and Sohal, 2003;Almansour, 2012;Kibe and Wanjau, 2014) identified the involvement of TQM practices with the quality and performances. (Joiner, 2007) concluded that there is a strong positive relationship between the extent of implementation of TQM practices and organization performance.…”
Section: Introductionmentioning
confidence: 99%